The Application of the Extended Thermodynamic Approach to Describe the Effect of Counterions, Both of Chaotropic Agents and Ionic Strength Modifiers, on the Retention Behavior of Protonated Basic Analytes in Chaotropic Chromatography - Gkountanas, Kostas; Rmandić, Milena; Protić, Ana; Malenović, Anđelija; Dotsikas, Yannis (Archives of Pharmacy, 2025)
In this study, the extended thermodynamic approach was used to quantitatively explain the effect of counterions, both of chaotropic agents and ionic strength modifiers, in variable (vI) and constant ionic strength (cI) systems on the retention behavior of 23 fully protonated basic analytes. Nine series of experiments (at three pH values for NaPF6, KPF6 and NH4PF6) with vI and nine series of experiments (at three pH values for NaPF6, KPF6 and NH4PF6) with ionic strength kept constant with NaCl, KCl and NH4Cl were performed. The experimentally determined retention factors were modeled using the extended thermodynamic approach and the processes occurring in the stationary phase and in the mobile phase and their influence on retention in the investigated chaotropic chromatography systems were rationalized. In both vI and cI systems, ion pair formation in the stationary phase proved to be dominant over ion pair formation in the mobile phase. In the KPF6_vI systems, these interactions with the stationary phase were even more pronounced than in the other systems. Although both K+ and NH4+ are chaotropic in nature, the formation of ion pairs in the stationary phase was favored by the presence of NH4+ only at its rather high concentrations as in cI systems.